University and Quality Systems. Evaluating faculty performance in face-to-face and online programs: A comparison of Likert and BARS instruments - Matosas-López, Luis; Leguey-Galán, Sonsoles; Ballesteros Regaña, Cristóbal; Pelicano Piris, Noelia (IJERI: International Journal of Educational Research and Innovation, 2024)
The assessment of faculty or teaching staff performance is key in quality systems in the university context. This assessment is usually done through student satisfaction surveys that use Likert or BARS (Behavioral Anchored Rating Scales) instruments to measure student perceptions of teaching staff effectiveness. This paper examines the ambiguity, clarity, and precision of these two types of instruments. The authors, using an experimental methodology and with the participation of 2,223 students from four Spanish universities, during six academic years (between 2019 and 2024), analyze the three aspects mentioned (ambiguity, clarity, and precision) in both types of questionnaires. The results confirm the existence of significant differences between the instruments. The results also show that although doubts about the ambiguity, lack of clarity and precision of Likert-type questionnaires are justified, these aspects can be improved by BARS-type instruments. The conclusions drawn invite administrators and policymakers, quality agencies, and university managers to consider which of these two instruments is more appropriate for gathering the information they need to make better decisions about faculty promotion.